Prevalence of functional bowel disorders and faecal incontinence: an Australian primary care survey. (February 2015) - Ng, K.‐S.; Nassar, N.; Hamd, K.; Nagarajah, A.; Gladman, M. A.
Abstract Aim Interest in functional bowel disorders (FBDs) and faecal incontinence (FI) has increased amongst coloproctologists. The study aimed to assess the prevalence of FBDs and FI (including its severity) among Australian primary healthcare seekers using objective criteria. Method A cross‐sectional survey was conducted in a primary care setting in Sydney, Australia. A self‐administered questionnaire was used to collect demographic information and diagnose FBDs (irritable bowel syndrome, constipation, functional bloating and functional diarrhoea) based on Rome III criteria. The severity of FI was determined using the Vaizey incontinence score. Associations with medical/surgical history and healthcare utilization were assessed. Results Of 596 subjects approached, 396 (66.4%) agreed to participate. Overall, 33% had FBD and/or FI. Irritable bowel syndrome was present in 11.1% and these participants were more likely to report anxiety/depression (P < 0.01) and to have had a previous colonoscopy (P < 0.001) or cholecystectomy (P = 0.02). Functional constipation was present in 8.1%, and functional bloating and functional diarrhoea were diagnosed in 6.1%, and 1.5%, respectively. FI was present in 12.1% with the majority (52%) reporting moderate/severe incontinence (Vaizey score > 8). Participants with FI were more likely to have irritable bowel syndrome, urinary incontinence and previous anal surgery (P < 0.01). Conclusion FBDs and FI are prevalent conditions amongst primary healthcare seekers and the needs of those affected appear to be complex given their coexisting symptoms and conditions. Currently, the majority do not reach colorectal services, although increased awareness by primary care providers could lead to sufferers being referred for specialist management.